Acupressure Techniques with Mom's Psychological Readiness in Facing Labor in the Area Poasia Puskesmas Kendari City - Wa Ode Putri Agustina Wahid; Sri Ramadhani; Mardiana Ahmad; Sri Wahyuni Bahrum (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Mother's brain research when confronting labor is exceptionally imperative for smooth conveyance so non-pharmacological strategies are required. The non-pharmacological strategy by implies of acupressure can offer assistance diminish labor torment. This research used a quasi-experimental method. The model used pretest-posttest. In this study, research subjects received acupressure training at the beginning of the third trimester. The investigate test was chosen utilizing the whole test method. So the test for this inquire about is 30 tests. The comes about appeared that the value of p=0,000 (p<0,05) means that factually there's a distinction within the availability of moms to confront childbirth some time recently and after instruction. The conclusion of the research is that education about the benefits of acupressure during childbirth will prepare research subjects.